UPAYA MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MATEMATIKA SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FASILITATOR AND EXPLAINING PADA SISWA KELAS VIII-A SMP NEGERI 14 MADIUN - Baru, Marisa; Santoso Yohanes, Rudi (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2019)
The purpose of this study was to find out the efforts to increase the activity and learning achievement of mathematics by using. Cooperative learning type Student Facilitator And Explaining (SFE) in Class VIII-A Students of SMP Negeri 14 Madiun. The results of the research that has been carried out are to increase the students' activeness and learning achievement of mathematics obtained conclusions as follows, (1) the percentage of the teaching teacher's ability to use the cooperative learning model type Student Facilitator and Explaining (SFE) in the first cycle of 2.65 has increased in the second cycle of 2.97. (2) the percentage of students' mathematics learning activeness during learning using the cooperative learning model type Student Facilitator and Explaining (SFE) in the first cycle of 32.14% experienced an increase in the second cycle by 50%. (3) the percentage of students' mathematics learning achievement tests in the first cycle of 20.83% experienced an increase in the second cycle of 58.33%. Cooperative learning type Student Facilitator and Explaining (SFE) has not been able to increase the activeness and achievement of mathematics learning of students, but experience an increase (change) from cycle I to cycle II.